The effects of CEO activism: Partisan consumer behavior and its duration - Hou, Young; Poliquin, Christopher W. (Strategic Management Journal, 2023)
Abstract Research Summary CEOs increasingly engage in activism on controversial social and political issues that do not directly affect their core business. Simultaneously, the general public is increasingly politically polarized. We examine how CEOs' support for gun control after two mass shootings differentially affected the behavior of liberal and conservative consumers and the persistence of these effects. Using mobile phone location data to measure store‐level visits, we find (a) consumer visits to stores decreased by 3%; (b) this decrease was asymmetric: visits in the most conservative counties decreased by about 5% but did not change in the most liberal counties; and (c) these effects dissipated within 10 weeks after activism. Our results highlight the strategic implications for executives pressured to take stances on controversial issues. Managerial Summary We study how consumers respond to CEO support for gun control, and how consumers' partisan views influence their behavior. Visits to the stores of several major retailers declined about 3% in the 4 weeks after their CEOs supported expanding background checks for gun purchases. In the most liberal counties, visits did not change following CEO support for gun control, while in the most conservative counties visits declined about 5%. Hence, the reaction of liberal consumers did not counteract the reaction of conservative consumers. We find, however, that these effects dissipated within 10 weeks; as a result, retailers whose CEOs supported gun control did not experience any long‐term, net decrease in sales despite the short‐term sales decrease in conservative counties.